Estimating the Distribution of Air Voids in Concrete (Civil Engineering Dimension, 2011)
Chord length measurements are used to estimate the volumetric distribution of air voids within hardened concrete samples. The accuracy of the Linear-Traverse method is questionable because chord lengths do not directly represent the actual volumes of the air voids. Using computer simulation, randomly generated concrete samples were analyzed using the Linear-Traverse method to compute the distribution of air voids, the chord length gradation curve, the chord length-to-traverse ratio, and the air void volume gradation curve. The current chord-length approach significantly underestimated the air void content. A method that estimates that air void gradation curve from the chord length gradation curve is presented. The computer simulation results are supported by a conceptual analysis. To obtain the most accurate estimate of the air void content, computer analyses showed that at least 15 traverse lines should be regularly spaced on the concrete sample.